Realism's Empire : Empiricism and Enchantment in the Nineteenth-Century Novel - Baker, Geoffrey, 1973- (Book collections on Project MUSE., 2009)
"In Realism's Empire: Empiricism and Enchantment in the Nineteenth-Century Novel, Geoffrey Baker demonstrates that realist fiction's stance toward both progress and the foreign or supernatural is much more complex than established scholarship has assumed. The work of Honoř de Balzac, Anthony Trollope, and Theodor Fontane explicitly laments the loss of mystery in the world due to increased knowledge and exploration. To counter this loss and to generate the complications required for narrative, these three authors import peripheral, usually colonial figures into the metropolitan centers they otherwise depict as disenchanted and rationalized: Paris, London, and Berlin. Baker's book examines the consequences of this duel for realist narrative and readers' understandings of its historical moment. In so doing, Baker shows Balzac, Trollope, and Fontane grappling with new realities that frustrate their inherited means of representation and oversee a significant shift in the development of the novel"--Publisher's description